Antimicrobial resistance of Streptococcus suis - Thuy Tien, Le Hong; Thuy Linh, Vu Thi; Quoc, Nguyen Bao (Academia Journal of Biology, 2016)
Streptococcus suis is one of the dangerous pathogens causing ruining effects on the swine industry. This pathogen can be transmitted from pigs to humans to induce meningitis, pneumonia, septicemia and even mortality. Uncontrolled antibiotic use is a potential risk of the increase of drug resistance of Streptococcus suis. This review will provide recent information of antibiotic resistance of Streptococcus suis worldwide and in Vietnam, together with an update of the molecular mechanisms of drug resistance. These information could be useful for effective prevention and treatment. Citation: Le Hong Thuy Tien, Vu Thi Thuy Linh, Nguyen Bao Quoc, 2017. Antimicrobial resistance of Streptococcus suis. Tap chi Sinh hoc, 39(2): 195-203. DOI: 10.15625/0866-7160/v39n1.7508 *Corresponding author: baoquoc@hcmuaf.edu.vn Received 10 December 2015, accepted 20 December 2016